Pembuatan Jamu Tradisional Kunyit Asam KKN Universitas Aufa Royhan Padang Sidimpuan di Kelurahan Pintu Padang II - Sindi A. Nasution; Dina Amelia; Anni Safitra; Alia Safitri; Yeyen Herlena (PAKAT: Jurnal Pengabdian Kepada Masyarakat, 2025)
The "back to nature" lifestyle is growing and gaining popularity. One commonly consumed herbal plant is turmeric. Turmeric (Curcuma longa L.), with its curkenin content, is reported to have therapeutic potential, including antibiotic, antiviral, and antioxidant properties. Turmeric is often combined with tamarind (Tamarindus indica) to create a turmeric and tamarind herbal drink. Tamarind also shows potential as an antidiabetic, antihyperlipidemic, and antioxidant. A community service program (KKN) program was held in collaboration with the community at Pintu Padang II, where students from Aufa Royhan University conducted training on the production of turmeric and tamarind herbal drink. Furthermore, these community members received valuable training, including the production of turmeric and tamarind herbal drink. In this area, there are no community groups producing turmeric and tamarind herbal drink. This is believed to be due to a lack of knowledge and skills in producing turmeric and tamarind drinks, particularly in the form of drinks or infusions. The community service program consisted of training on traditional medicine, followed by hands-on production of turmeric and tamarind herbal drink. The results showed that the community understood the definition, classification, and labeling of traditional medicines, as well as the preparation of the herbal medicine turmeric usam. This was evidenced by the increased knowledge gained when asked questions about traditional medicines and how to make instant turmeric and tamarind herbal medicine.